Framework to Evaluate Quality Performance of Green Building Delivery: Project Brief and Design Stage - Ayman Raouf (19541692) (2021)
Design quality considers the extent to which the owner’s requirements are accurately synthesized into conformance specifications and drawings for the construction team to execute. Expected superior performance and sustainability of a green building require diligence in design to ensure its specifications are accurately stipulated. Several studies reported mismatches between expected and actual performances in green buildings that were attributed to poor design. This study thus revisits the design process and proposes a framework to map the quality activities in the project brief and design stages using the integration definition for function modeling (IDEFO) process. Semi-structured interviews and a focus group validated the framework and revealed issues in the current design practice that cause insufficient design solutions. Additionally, project delivery systems were discussed, with conditions for improving their suitability. This research contribution elucidates recommended quality activities necessary for green buildings, which often are not implemented in the construction industry, to ultimately ensure that green buildings are properly designed to meet sustainability objectives. Other Information Published in: Buildings License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/buildings11100473